The Correlation between Lung Ultrasound and Pathology in Rat Model of Monocrotaline-Induced Pulmonary Hypertension - Yan-Fen Zhong; Bin-Bin Liang; Xiao-Feng Zhang; null Ji-Wu (Canadian Respiratory Journal)
Pulmonary hypertension (PH) is a progressive and complex pulmonary vascular disease with poor prognosis. The aim of this study was to provide a new understanding of the lung pathology of disease and a noninvasive method in monitoring the establishment of animal models for basic and clinical studies of PH, indeed to explore clinical application value of lung ultrasound for patients with PH. Totally 32 male SD rats were randomly divided into control group, MCT (monocrotaline) group, PDTC (pyrrolidine dithiocarbamate) group, and NS (normal saline) group. Rats in the MCT group, PDTC group, and NS group received single intraperitoneal injection of MCT, while the control group received the same dose of NS. Then, PDTC group and NS group received PDTC and NS daily for treatment at the end of the model. Each group received lung ultrasound examination and measurement of pulmonary arterial pressure (PAP). Then, the rats were sacrificed to take the lung specimens to being observed. The ultrasound and pathological results were analyzed with a semiquantitative score. With the pulmonary artery pressure increases, the MCT group had a higher pulmonary ultrasound score and pathological score compared with the control group (p<0.05). After PDTC treatment, the pulmonary ultrasound score and the pathological score decline (p<0.05). We investigated both lung ultrasound scores, and the pathological scores were positively correlated with mean pulmonary artery pressure (mPAP) (both r > 0.8, p<0.0001). Moreover, lung ultrasound scores were positively correlated with pathological scores (r > 0.8, p<0.0001). We elucidated lung ultrasound evaluation providing more evidence for the management of PH in the rat model. Moreover, lung ultrasound provided a noninvasive method in monitoring the establishment of animal models for basic and clinical studies of PH.